Histomorphometric study on the effects of Artemisia sieberi extract in mice skin - Kaboutari Jahangir; Haydarnejad Mohammad Saeed; Fatahian Dehkordi Rahmat allah; Raeisi Vanani Sedigheh (Shahrekord University of Medical Sciences, 2015)
Introduction: Skin as the biggest single body organ is always exposing to various injuries, therefore health and healing of its injuries is vital. Artemisia sieberi is a valuable medicinal plant with a long history of indication in folk and modern medicine. Due to different chemical components and antioxidant, anti-inflammatory, antimicrobial and cytoprotective properties of Artemisia, this study was conducted to study the histomorphometric effects of Artemisia sieberi (A. sieberi) extract on mice skin. Methods: Ninety adult mice were randomly divided in 3 groups. In the treatment group A. sieberi extract dissolved in ethanol & distilled water, in the positive control ethanol & distilled water, and in negative control only distilled water were applied on the shaved dorsum twice daily for 21 days. Mean thickness of epidermis, hypodermis & dermis layers, percentage of collagen fibers and histological evaluation of skin layers were studied in 1, 3, 5, 14 and 21days post treatment. Data were presented as mean± SD and analyzed using one way ANOVA and LSD post hoc tests. The P<0.05 was considered as statistically significant. Results: A. sieberi extract significantly increased epidermis thickness in day 1, hypodermis, dermis and percentage of collagen fibers in day 3 in comparison to positive and negative control groups. Histology study revealed normal structure of skin and no abnormality was seen. Conclusion: A. sieberi extract can be effective for health and healing of skin injuries by increasing thickness of the skin layers and amount of collagen fibers.